Czynniki socjologiczne a przestępczość kobiet. Wybrane teorie kryminologiczne - Sitnik, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
This article aims to present selected sociological theories of female crime. The sociological direction seeks sources of crime in the social factors. The paper presents the theories that are important from the point of view of the cognitive causes of female crime and provide information that is necessary to know the etiology of criminal behavior.
Keywords: teorie socjologiczne; przestępczość kobiet; kryminologia